Properties and physiological effects of dietary fiber-enriched meat products: a review - Mishra, Bidyut Prava; Mishra, Jyotiprabha; Paital, Biswaranjan; Rath, Prasana Kumar; Jena, Manoj Kumar; Reddy, B. V. Vivekananda; Pati, Prasad Kumar; Panda, Susen Kumar; Sahoo, Dipak Kumar (Frontiers in Nutrition, 2023)
About 86% of people consume meat in their daily diet. In most meat-consuming countries (about 9% of countries that include 1.8 billion people), about 100 g of unprocessed red meat is consumed daily in their diet. And people of about 17% of countries (about 520 million people) have a meat intake of 50 g meat per day. So, meat is an essential part of daily diets in many countries that provides an easy source of protein. However, this important food does not contain dietary fibers. Therefore, it has been a new concept to add dietary fibers to meat to fortify its food value since the last decades. The current review focuses on various dietary fibers and their physiological effects associated with dietary fibers. The influence of dietary fibers on the physicochemical properties, chemical composition, textural properties, colour parameters, sensory properties, and fatty acid composition, along with their role in several diseases, including cardiovascular, cancer, and diabetes of the meat products fortified with dietary fibers, are emphatically covered.